Raman Fingerprints of SARS-CoV‑2 Omicron Subvariants: Molecular Roots of Virological Characteristics and Evolutionary Directions - Pezzotti, Giuseppe; Ohgitani, Eriko; Fujita, Yuki; Imamura, Hayata; Pappone, Francesco; Grillo, Alfio; Nakashio, Maiko; Shin-Ya, Masaharu; Adachi, Tetsuya; Yamamoto, Toshiro; Kanamura, Narisato; Marin, Elia; et al. (ACS infectious diseases, 2023)
The latest RNA genomic mutation of SARS-CoV-2 virus, termed the Omicron variant, has generated a stream of highly contagious and antibody-resistant strains, which in turn led to classifying Omicron as a variant of concern. We systematically collected Raman spectra from six Omicron subvariants available in Japan (i.e., BA.1.18, BA.2, BA.4, BA.5, XE, and BA.2.75) and applied machine-learning algorithms to decrypt their structural characteristics at the molecular scale. Unique Raman fingerprints of sulfur-containing amino acid rotamers, RNA purines and pyrimidines, tyrosine phenol ring configurations, and secondary protein structures clearly differentiated the six Omicron subvariants. These spectral characteristics, which were linked to infectiousness, transmissibility, and propensity for immune evasion, revealed evolutionary motifs to be compared with the outputs of genomic studies. The availability of a Raman “metabolomic snapshot”, which was then translated into a barcode to enable a prompt subvariant identification, opened the way to rationalize in real-time SARS-CoV-2 activity and variability. As a proof of concept, we applied the Raman barcode procedure to a nasal swab sample retrieved from a SARS-CoV-2 patient and identified its Omicron subvariant by coupling a commercially available magnetic bead technology with our newly developed Raman analyses.